Bilateral posterior central corneal steepening with decreased visual acuity. Issue 4 (April 2022) - Sugar, Joel; Afshari, Natalie; Moon, Jared; Bowden, Eileen; Kim, Gene; Karimian, Farid; Murri, Michael; Jacob, Soosan
Abstract : A 40-year-old woman was referred for the assessment of bilateral corneal opacities with gradual visual decline over the course of the past decade. Abstract : A 40-year-old woman was referred for the assessment of bilateral corneal opacities with gradual visual decline over the course of the past decade. Her past ocular history is significant for bilateral amblyopia and strabismus surgery in both eyes before age 5. The patient's parents were told by her childhood ophthalmologist that she had a hereditary disorder. Her systemic review was significant for anal fissure and human leukocyte antigen-B27 ankylosing spondylitis. Her past ocular record revealed corrected distance visual acuity (CDVA) of 20/80 in both eyes in 2018 with central corneal haze. On presentation, her uncorrected distance visual acuity was 20/150 in both eyes. Her CDVA was 20/100 in both eyes with manifest refraction of +0.50 −2.50 × 075 in the right eye and +5.00 −2.25 × 094 in the left eye. Corneal topography reflected keratometry of 35.75/38.97 × 171 in the right eye and 36.45/38.35 × 32 in the left eye. Central corneal thickness was 669 μm and 652 μm, respectively. External slitlamp examination revealed a central faint stromal opacity inferior to the visual axis in the right eye and a central faint stromal opacity in the left eye, and both were associated with steep posterior curvature of the cornea (Figure 1). Further findings included 0.5 corneal haze with mild guttata, normal irides, and clear lenses in both eyes. Intraocular pressure was 23 mm Hg and 26 mm Hg, respectively (Figure 2, Supplemental Figures 1 and 2, http://links.lww.com/JRS/A543 ). Gonioscopy was unremarkable. Dilated fundus examination revealed a 0.15 cup-to-disc ratio bilaterally, but otherwise no pertinent vitreoretinal pathologies were noted. What is the most likely diagnosis? What medical or surgical interventions would you recommend for this patient? What is the prognosis for this patient?